ANALISIS PENGARUH KREATIVITAS IKLAN, DAYA TARIK IKLAN DAN Kualitas pesan iklan terhadap brand attitude pada produk Blackberry Z10 di kota Pekanbaru - Rahmadawita, Tuti; Sulistyowati, Lilis; ', Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the influence analysis advertising creativity, attractiveness and quality of advertising on brand attitude advertising messages on Blackberry Z10 products in the city of Pekanbaru. Inside The study consisted of a dependent variable that brand attitude (Y), and three independent variables consisting of advertising creativity (X1), advertising appeal (X2), and the quality of the advertising message (X3). Population of this study is the city of Pekanbaru with a sample of 100 respondents aged 15-30 years with criteria've watched ads Blackberry Z10. This study uses a sampling technique that is purposive sampling and analysis of research data using qualitative methods, quantitative and multiple regression equations with the help of SPSS (Statistic Services For Product and Solution).From the results of this study showed that advertising creativity, attractiveness and quality of advertising on brand attitude advertising messages on Blackberry Z10 products have a significant effect on the city of Pekanbaru. Of r square calculation method indicates that advertising creativity, attractiveness and quality of advertising messages advertising berpenagruh of sixty-six point eight percent on brand attitude remaining thirty-three point two percent influenced by other variables not examined in this study.Keywords: Brand Attitude, Creativity in Advertising, Fascination Advertising, Advertising Message Quality.